Kinetics of Oxidation of Acetophenone Oxime byPyridinium Fluorochromate - KAMBLE, V.M.; JOSHI, S.B. (Asian Journal of Chemistry, 2010)
Kinetics of the oxidation of acetophenone-oxime and its p-substituted derivatives by pyridinium fluorochromate has been studied at 30°C. The product analysis indicates that the reaction is oxidative hydrolysis. The rate increases with the increase in concentration of hydrogen ions. The first order rate dependence on the substrates. The effect of temperature, solvent, perchloric acid and sodium perchlorate has been studied. The activation energy and other thermodynamic parameters are determined.